1988
DOI: 10.1007/bf01321005
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus morphogenesis: an ultrastructural study of the late cytoplasmic phases

Abstract: The late cytoplasmic phases of human Cytomegalovirus (HCMV) morphogenesis in cultured fibroblasts have been studied by transmission electron microscopy focusing attention on the relationship between the viral particles and host cell organelles. The results obtained largely reflect changes in cells subjected to sublethal injurious stimuli induced by many viruses as well as different noxious agents. A great increase in the number of Golgi apparatuses and lysosomes was observed, both of them interacting with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
1
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 49 publications
(52 reference statements)
7
69
1
1
Order By: Relevance
“…3B) showed that SNAP-23 was spread through the cytoplasm in mock-infected cells, presumably owing to its association with vimentin filaments (29). In contrast, at 96 hpi, a substantial portion of SNAP-23 colocalized with pUL99 and pUL55 (gB), markers for the HCMV assembly compartment, the site at which the virion acquires an envelope (9)(10)(11)(12).…”
Section: Virion Glycerophospholipid Composition Is Different From Thamentioning
confidence: 99%
See 1 more Smart Citation
“…3B) showed that SNAP-23 was spread through the cytoplasm in mock-infected cells, presumably owing to its association with vimentin filaments (29). In contrast, at 96 hpi, a substantial portion of SNAP-23 colocalized with pUL99 and pUL55 (gB), markers for the HCMV assembly compartment, the site at which the virion acquires an envelope (9)(10)(11)(12).…”
Section: Virion Glycerophospholipid Composition Is Different From Thamentioning
confidence: 99%
“…Newly synthesized membranes likely accumulate in the assembly compartment (4)(5)(6)(7)(8), a virus-induced organelle with virus-coded proteins and cellular proteins that include markers of the exocytic and endocytic networks. This is the site at which viral capsids acquire an envelope (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…The late cytopathic effect in the cytoplasm is characterized by a rearrangement of the Golgi complex and accumulation of membrane cisternae and viral particles in the vicinity of the centrosome, referred to as the viroplasm (Severi et al, 1988). At that stage, envelopment of progeny is seen to occur in association with the tubular endosome which was visualized by uptake of fluid phase marker HRP (Fig.…”
Section: Maturation Of Cytoplasmic Progeny Virions Is Blocked In Ul32mentioning
confidence: 99%
“…could represent incorporation of a virally modified normal cell component during particle assembly. Envelopment of CMV nucleocapsids was originally thought to occur at the internal nuclear membrane (Smith & de Harven, 1973), but recent electron microscopic studies favour acquisition of the final envelope in the Golgi apparatus region of infected cells (Severi et al, 1988) and occasionally at the plasma membrane (Landini et al, 1987). It is therefore plausible that during envelopment, both virally modified and unmodified normal membrane constituents are incorporated into the viral envelope.…”
Section: K--mentioning
confidence: 99%